New Ionic Liquid Microemulsion-Mediated Synthesis of Silver Nanoparticles for Skin Bacterial Infection Treatments - Fayez Althobaiti; Ola A. Abu Ali; Islam Kamal; Mohammad Y. Alfaifi; Ali A. Shati; Eman Fayad; Serag Eldin I. Elbehairi; Reda F. M. Elshaarawy; W. Abd El-Fattah (MDPI AG, 2023)
This work reports a new approach for the synthesis of extremely small monodispersed silver nanoparticles (AgNPs) (2.9-1.5) by reduction of silver nitrate in a new series of benzyl alkyl imidazolium ionic liquids (BAIILs)-based microemulsions (3a-f) as media and stabilizing agents. Interestingly, AgNPs isolated from the IILMEs bearing the bulkiest substituents (tert-butyl and n-butyl) (3f) displayed almost no nanoparticle agglomeration. In an in vitro antibacterial test against ESKAPE pathogens, all AgNPs-BAIILs had potent antibiotic activity, as reflected by antibacterial efficiency indices. Furthermore, when compared to other nanoparticles, these were the most effective in preventing biofilm formation by the tested bacterial strains. Moreover, the MTT assay was used to determine the cytotoxicity of novel AgNPs-BAIILs on healthy human skin fibroblast (HSF) cell lines. The MTT assay revealed that novel AgNPs-BAIILs showed no significant toxic effects on the healthy cells. Thus, the novel AgNPs-BAIILs microemulsions could be used as safe antibiotics for skin bacterial infection treatments. AgNPs isolated from BAIIL (3c) was found to be the most effective antibiotic of the nanoparticles examined.